Penerapan Metode Motion Graphic pada Video Promosi Rumah Kos Dermawan Living, Denpasar Bali - Ni Putu Virginia A.S; Karna Mustaqim (MES Bogor, 2024)
In this research, the application of the motion graphic method in making promotional videos for the Dermawan Living Boarding House in Denpasar, Bali, was explored. Motion graphics, as a visual technique that combines graphic elements, animation and text, are used to create dynamic and interesting messages. The research method involves analysing promotional videos before and after the implementation of motion graphics. Audience response, engagement level, and recall of the video are measured. The research results show that the application of motion graphics significantly increases the attractiveness of promotional videos. The use of dynamic visual elements and smooth transitions makes videos more interesting and memorable for the audience. Apart from that, motion graphics also help convey information more efficiently. In conclusion, the use of motion graphic methods in promotional videos can be an effective strategy for increasing attractiveness and communication efficiency. The practical guidance resulting from this research can help content creators optimize the use of motion graphics in promotional videos.